Efficacy of modified pressure cuff for thrombolytic treatment on lower extremity deep venous thrombosis. Issue 17 (30th April 2021) - Li, Yan; Sutedjo, Janesya; Chen, Yu-Chen; Gu, Jian-Ping
Abstract : Abstract: To compare the effectiveness and patient comfort between two methods that block superficial venous blood flow during the thrombolytic treatment of lower extremity deep venous thrombosis (DVT) to provide evidence that informs clinical choice. One hundred twenty patients with lower extremity DVT were randomly divided into sphygmomanometer (group A, n = 40), tourniquet (group B, n = 40), and control group (no blocking, n = 40). All the patients were treated with a daily dosage of urokinase using a dial sphygmomanometer cuff and tourniquet to block lower extremity superficial vein blood flow. The pressure of the dial sphygmomanometer blocking lower extremity superficial vein blood flow was measured during lower extremity venography. Leg swelling reduction rate, venous patency, thrombus removal rate, and average comfort index were observed during the blocking process. The average pressure value for group A was 70 ± 10 mm Hg. The differences in the swelling reduction rate and venous patency were significant between the groups. Comparing the two groups at different time points, the average thrombus clearance rate of group A was higher than that of group B and control group. The leg pain scores of group A were lower than those of group B and control group. The postoperative comfort ratio of group A was higher than that of group B, and the proportion of severe discomfort in group A was lower than that in group B. Compared with the tourniquet, using a dial sphygmomanometer cuff to block lower extremity superficial vein blood flow achieved a better thrombolytic effect on DVT and provided higher patient comfort during treatment.